A novel reductive graphene oxide‐based magnetic molecularly imprinted poly(ethylene‐co‐vinyl alcohol) polymers for the enrichment and determination of polychlorinated biphenyls in fish samples. Issue 6 (3rd March 2015) - Lin, Saichai; Gan, Ning; Zhang, Jiabin; Chen, Xidong; Cao, Yuting; Li, Tianhua
Abstract : The novel reductive graphene oxide‐based magnetic molecularly imprinted poly(ethylene‐ co ‐vinyl alcohol) polymers (rGO@m‐MIPs) were successfully synthesized as adsorbents for six kinds of polychlorinated biphenyls (PCBs) in fish samples. rGO@m‐MIPs was prepared by surface molecular imprinting technique. Besides, Fe3 O4 nanoparticles (NPs) were employed as magnetic supporters, and rGO@Fe3 O4 was in situ synthesis. Different from functional monomer and cross‐linker in traditional molecularly imprinted polymer, here, 3, 4‐dichlorobenzidine was employed as dummy molecular and poly(ethylene‐ co ‐vinyl alcohol) was adopted as the imprinted polymers. After morphology and inner structure of the magnetic adsorbent were characterized, the adsorbent was employed for disperse solid phase extraction toward PCBs and exhibited great selectivity and high adsorption efficiency. This material was verified by determination of PCBs in fish samples combined with gas chromatography‐mass spectrometry (GC‐MS) method. According to the detection, the low detection limits (LODs) of PCBs were 0.0035–0.0070 µg l −1 and spiked recoveries ranged between 79.90 and 94.23%. The prepared adsorbent can be renewable for at least 16 times and expected to be a new material for the enrichment and determination of PCBs from contaminated fish samples. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Fe3 O4 nanoparticles (NPs) were used as magnetic supporters, and rGO@Fe3 O4 was in situ synthesis. Different from functional monomer and cross‐linker in traditional molecularly imprinted polymer, 3, 4‐dichlorobenzidine was employed as dummy molecular that has the similar skeletal structure with PCBs. Furthermore, one‐pot synthesis of rGO@m‐MIPs was employed in this work. The prepared rGO@m‐MIPs could absorb PCBs in fish selectively and quantitively.